Peran Informasi Akuntansi dan Pengendalian Internal dalam Keberlanjutan UMKM Kabupaten Kubu Raya - Afif, Ali; Jaurino, Jaurino; Mayasafitri, Rina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Digital transformation through accounting information systems plays an important role in driving the sustainability of MSMEs. By allowing MSMEs to streamline their operations. In addition, it is time for internal control to be considered important for MSME-scale businesses. The development of MSMEs requires stakeholders to understand their finances and be able to manage them efficiently and effectively. Efficient and effective financial management aims to ensure business continuity. The objective of this study is to produce and present in-depth information on how accounting information systems and internal controls work. The method used in this research is the quantitative method. Primary data collection was conducted by distributing questionnaires to MSME actors, which were then analyzed using SmartPLS to describe the relationships within the research model. The research results indicate that accounting information and internal control have an impact on the Sustainability.